Obstetric Outcome of Subsequent Pregnancy Following Intrauterine Death - Al –Bassam, Anwar N.; Khunda, Sarmad S.; Hussam, EKhlas (Journal of the Faculty of Medicine Baghdad, 2011)
Background :Intrauterine foetal death is defined by World Health Organization (WHO) as ‘death prior to complete expulsion or extraction from its mother of a product of conception, irrespective of the duration of pregnancy; the death is indicated by the fact that after such separation the fetus does not breath or show any other evidence of life. Objective: The aim of the study is to assess obstetric outcome in the subsequent pregnancy in comparison with that following live birth in first pregnancy.Patients and methods: A cross sectional, observational study carried out in department of Obstetrics and Gynaecology of Baghdad Teaching Hospital. during the period from March 2008 to April 2009 The studied group include 53 women in their second pregnancy whom first pregnancy were ended by vaginal delivery of a dead foetus and 489 women delivered a live birth in first pregnancy (labelled as control group). Results: Women in the studied group (n=53) were at increased risk of miscarriage (p=0.005), preeclampsia (p=0.004), low birth weight (p=0.0001), induction of labour (p=0.0004), emergency CS (P=0.003), Elective CS (p=0.027), stillbirths (p=0.0006) as compared with the control group.Conclusion: While the majority of women with previous stillbirth have alive birth in the subsequent pregnancy, they are a high –risk group with an increased incidence of adverse maternal and neonatal outcomes. .